TERMINOLOGI MANUSIA BERDASARKAN DI DALAM AL-QUR’AN: Istilah Manusia dalam al-quran - Ahmad Farid; Siti Nurmalasari; Siti Mukhayaroh; Magfhfiroh, Latifatul (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Abstract.Allah SWT created humans in this world as a manifestation of His existence as the Creator of all His creatures, leading to obedience and devotion in the form of worship. In the Qur'an there are three themes that focus on human designations, namely a). Al-Basyar, especially from a physical or biological perspective (b). Al-Nas, namely humans according to their social point of view, and (c) Al-Ins or Al-Insan, namely humans according to their position and character. By remembering the position of humans as kings on earth and servants of Allah SWT, humans are blessed with the power of reasoning, knowledge, and the ability to distinguish between right and wrong, thus making them more